Technique for measuring convective heat transfer at rough surfaces - Wang, Z; Ireland, P; Jones, T (Publ by ASME, 1990)
A new method has been developed for measuring local heat transfer coefficients at rough surfaces. The technique was applied to an idealised section of a large scaled model of a turbine blade cooling passage to assess the effect of surface irregularities which result from the blade manufacturing process. The experimental method is described in full and the results are presented for tests on an isolated pin-fin situated in fully developed channel flow. The effect of the thermal conductivity of the roughness elements is discussed.